2021
DOI: 10.3390/jcm10040704
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Dynamic Computer-Assisted Implant Placement: A Systematic Review and Meta-Analysis of Clinical and In Vitro Studies

Abstract: The aim of this systematic review and meta-analysis is to analyze the accuracy of implant placement using computer-assisted dynamic navigation procedures. An electronic literature search was carried out, supplemented by a manual search. The literature search was completed in June 2020. The results of in vitro and clinical studies were recorded separately from each other. For inclusion in the review, the studies had to examine at least the prosthetically relevant parameters for angle deviation, as well as globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 65 publications
4
33
1
Order By: Relevance
“…The evaluation of the angular deviation in the present study showed a mean deviation of 2.7° (95% CI, 2.2°–3.3°). These values showed a similar precision compared to the majority of studies published to date [ 31 ]. The angular deviations reported in these studies were between 3.68° (95% CI, 3.61°–3.74°) [ 43 ] and 4.22° (95% CI, 2.74°–5.68°) [ 44 ].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The evaluation of the angular deviation in the present study showed a mean deviation of 2.7° (95% CI, 2.2°–3.3°). These values showed a similar precision compared to the majority of studies published to date [ 31 ]. The angular deviations reported in these studies were between 3.68° (95% CI, 3.61°–3.74°) [ 43 ] and 4.22° (95% CI, 2.74°–5.68°) [ 44 ].…”
Section: Discussionsupporting
confidence: 77%
“…Previously published data on the accuracy of dynamic navigation were analyzed in three systematic reviews. On average, the coronal 3D deviation at the implant shoulder was between 1.00 mm (95% CI 0.83, 1.16 mm) and 1.11 mm (95% CI 0.96, 1.26 mm) [ 31 , 43 , 44 ]. The implant exit point is particularly important for prosthetically predictable results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Template-guided implant placement has proven to be a reliable static computer-assisted surgical method. A further dynamic procedure is real-time navigation [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Both DICOM files were imported to the robotic surgery verification system, and this registration process was further performed. In addition, the errors between the planned and placed implant positions were measured, as previously described in detail [ 20 , 21 ]. Based on the central axis of the planned and placed implants, the accuracy data showed the distance deviation in mm, including the global coronal deviation, vertical coronal deviation, lateral coronal deviation, global apical deviation, vertical apical deviation, and lateral apical deviation, respectively ( Figure 7 ).…”
Section: Methodsmentioning
confidence: 99%